2011
DOI: 10.1242/jcs.075325
|View full text |Cite
|
Sign up to set email alerts
|

UV-induced photolesions elicit ATR-kinase-dependent signaling in non-cycling cells through nucleotide excision repair-dependent and -independent pathways

Abstract: Activation of signaling pathways by UV radiation is a key event in the DNA damage response and initiated by different cellular processes. Here we show that non-cycling cells proficient in nucleotide excision repair (NER) initiate a rapid but transient activation of the damage response proteins p53 and H2AX; by contrast, NER-deficient cells display delayed but persistent signaling and inhibition of cell cycle progression upon release from G0 phase. In the absence of repair, UV-induced checkpoint activation coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 64 publications
6
85
1
1
Order By: Relevance
“…We used GGR-deficient XPC-negative cells to ensure that, within locally UV-exposed cell nuclei, repair replication was exclusively due to ongoing TCR. In combination with γ-H2AX immunofluorescence labeling (17,24,25) for precise localization of UV-induced DNA-damaged areas, we quantified repair replication in those areas via incorporation of a fluorophore-coupled deoxynucleoside analog into newly synthesized DNA (22) (Fig. 4A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used GGR-deficient XPC-negative cells to ensure that, within locally UV-exposed cell nuclei, repair replication was exclusively due to ongoing TCR. In combination with γ-H2AX immunofluorescence labeling (17,24,25) for precise localization of UV-induced DNA-damaged areas, we quantified repair replication in those areas via incorporation of a fluorophore-coupled deoxynucleoside analog into newly synthesized DNA (22) (Fig. 4A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although ATR activation has been suggested to occur in non-cycling cells (25)(26)(27)(28)(29)(30)(31)(32)(33), its signaling function has not been extensively examined and its bona fide substrates are not known. Thus, to examine the role of ATR kinase activity in DNA damage signaling in non-cycling cells, we made use of the highly selective ATR inhibitor VE-821 (21,53).…”
Section: Atr Contributes To Dna Damage Response Protein Phosphorylatimentioning
confidence: 99%
“…Although previous studies have indicated that ATR can be activated in noncycling cells in response to DNA repair intermediates (25)(26)(27)(28)(29)(30)(31)(32) and in response to the stalling of RNA polymerase (33)(34)(35), the functional significance of ATR in these contexts in non-cycling cells has not been examined.…”
mentioning
confidence: 99%
“…For example, stalled RNA polymerase II may stimulate p53-mediated apoptosis via ATR, even in the absence of replication [148][149][150], possibly via accumulation of RPA on regions of single-stranded DNA [151]. Activation of PARP at SSBs can trigger another mechanism of cell death.…”
Section: Single-strand Lesions and Neuronal Cell Deathmentioning
confidence: 99%